Impact of human resource management practices on the financial and operational performance of commercial banks listed on the Nigerian Stock Exchange - Akalezi, Uchendu Nicholas (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMil)--Stellenbosch University, 2024.